2022
DOI: 10.1364/boe.461433
|View full text |Cite
|
Sign up to set email alerts
|

Label-free metabolic imaging of non-alcoholic-fatty-liver-disease (NAFLD) liver by volumetric dynamic optical coherence tomography

Abstract: Label-free metabolic imaging of non-alcoholic fatty liver disease (NAFLD) mouse liver is demonstrated ex vivo by dynamic optical coherence tomography (OCT). The NAFLD mouse is a methionine choline-deficient (MCD)-diet model, and two mice fed the MCD diet for 1 and 2 weeks are involved in addition to a normal-diet mouse. The dynamic OCT is based on repeating raster scan and logarithmic intensity variance (LIV) analysis that enables volumetric metabolic imaging with a standard-speed (50,000 A-lines/s) OCT system… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 68 publications
1
16
0
Order By: Relevance
“…Simultaneously obtained birefringence images show that the birefringence of the liver of the 1-week NAFLD model is higher than that of the normal liver, and it becomes low again in the liver of 2-week NAFLD model mouse as shown in Fig. 12 (c-d) [127].…”
Section: E Ex Vivo and In Vitro Tissue Imagingmentioning
confidence: 82%
See 1 more Smart Citation
“…Simultaneously obtained birefringence images show that the birefringence of the liver of the 1-week NAFLD model is higher than that of the normal liver, and it becomes low again in the liver of 2-week NAFLD model mouse as shown in Fig. 12 (c-d) [127].…”
Section: E Ex Vivo and In Vitro Tissue Imagingmentioning
confidence: 82%
“…The structure and activities of the microvascular 11 [126]. The D-OCT (LIV) investigation of normal and non-alcoholic-fatty-liver-disease (NAFLD) model mouse livers has revealed the high activity of lipid droplets, zonation structures, and inflammation that were not visible in conventional OCT imaging [127]. Here, the NAFLD models were 1-week and 2-week methionine cholinedeficient (MCD)-diet models, which were fed with a MCD diet for 1 and 2 weeks.…”
Section: E Ex Vivo and In Vitro Tissue Imagingmentioning
confidence: 99%
“…In the standard OCT intensity, the structure of the renal tissue cannot be identified and the tissue appears homogeneous [Figs. 1(a) vivo liver study 30 . In the LIV en face slice, small structural formations (yellow arrows) and some spatially isolated high-LIV spots (white arrowheads) are visible [Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Several DOCT methods have been demonstrated to visualize the magnitude [28,29], frequency [30][31][32], and time-correlation [28,33,34] of the intratissue and intracellular activities. DOCT has been applied to a variety of samples including human esophageal and cervical biopsies [32], ex vivo mouse or rat organs [29][30][31][34][35][36], in vivo zebrafish [37], in vitro cell culture [38], spheroid [28,39], mammaria organoid [40], and retinal organoid [41]. Among the DOCT techniques, logarithmic-intensity-variance (LIV) contrasts the fluctuation magnitude of the OCT signal intensity [28], and is expected to be sensitive to the magnitude of intratissue and intracellular motility.…”
Section: Introductionmentioning
confidence: 99%
“…Among the DOCT techniques, logarithmic-intensity-variance (LIV) contrasts the fluctuation magnitude of the OCT signal intensity [28], and is expected to be sensitive to the magnitude of intratissue and intracellular motility. In previous studies, LIV has revealed the functional structures of ex vivo mouse organs [35,36] and in vitro tumor spheroids [28,39].…”
Section: Introductionmentioning
confidence: 99%